Model prediction of indoor particle concentrations in a public school classroom - Tippayawong N. (2014)
Indoor particle concentration and its relationship with outdoor particle level were investigated using a macroscopic indoor air quality model for a classroom ventilated naturally. The model was validated with measurement data obtained from an optical particle analyzer's measurements. Reasonably good agreement between the predicted results and measurements was demonstrated. The regression curves between modeling and measurement have slopes of 0.78 - 1.29 and correlation coefficients (R2) of 0.78 - 0.91, for the size range between 0.3 to 5.0 μm. The effect of air exchange rate on indoor/outdoor concentration ratios was also studied. The model simulations suggested that indoor and outdoor air exchange had direct influence on indoor PM concentration. For high outdoor concentrations, low air exchange rates could reduce the concentration levels of particles indoors. The results were found to compare well with those reported in the literature.